Subjective intensity of pain during ultrasonic supragingival calculus removal - Andreas Braun (Blackwell Synergy, 2007)
Objective: To assess subjective intensities of pain during supragingival calculus removal employing ultrasonic scaler tips of two different shapes. Material and Methods: Twenty patients were treated using a piezoelectric ultrasonic device (Sirosonic L) and two different scaler tips representing a conventional (Instrument No. 3) and a slim-line style (Perio Pro Line Instrument SI-11) in a split-mouth design. Pain was recorded during calculus removal at intervals of 0.5 s employing an inter-modal intensity comparison. Additionally, a visual analogue scale was used for evaluation directly after the treatment procedure. Treatment time was recorded to assess the efficiency of calculus removal. Results: Pain assessment during treatment showed that the slim-line scaler tip (median pain score: 1.4 [U], maximum: 3.5 [U], minimum: 0 [U]) caused less pain than the conventional device (median pain score: 7.8 [U], maximum: 14.7 [U], minimum: 0 [U]) (po0.05). These results could be confirmed by the visual analogue scale. Treatment with the slim-line tip took significantly longer than treatment with the conventional tip (po0.05). Conclusions: Using slim-line-styled ultrasonic scaler tips for supragingival calculus removal, painful sensations can be reduced compared with conventional ultrasonic devices. Thus, it might be possible to increase the patient’s compliance during dental treatment with oscillating instruments.